Body Trust, agitation, and suicidal ideation in a clinical eating disorder sample. Issue 10 (23rd July 2020) - Duffy, Mary E.; Lieberman, Amy; Siegfried, Nicole; Henretty, Jennifer R.; Bass, Garrett; Cox, Shelbi A.; Joiner, Thomas E.
Abstract: Objective: Research has established pairwise relationships between suicidal ideation (SI), low Body Trust, elevated agitation, and eating disorders, but knowledge of how these aspects relate in a single model is lacking. This study tested an indirect pathway with low Body Trust relating to severity of SI via agitation in a clinical eating disorder sample. Method: Participants ( N = 319; 92.8% female; 93.4% Caucasian; mean age 21.8 years) were adults currently receiving specialized eating disorder treatment (44.3% intensive outpatient or higher level‐of‐care) who completed online self‐report measures of study variables. The PROCESS macro was utilized to test proposed pathways. Results: Low Body Trust was significantly directly associated with increased severity of current SI, both before ( B = −.89, p < .001) and after ( B = −.51, p = .001) accounting for the indirect effect through agitation, also significant ( B = −.37, SE = .06, CI −.52 to −.26). Discussion: Perception of the body as unsafe may be related to agitation, and this intolerable sensation of trapped arousal could contribute to a desire to die. Future work should investigate these relationships prospectively to determine the relevance of Body Trust for assessment and treatment of suicide‐related factors among individuals with eating disorders.